Analysis of Employee Work Productivity at PT Indospray Perkasa Karawang - Fachyumi, Vieka Nurlita; Mohammad Darul Fadli, Uus; Ery , Rosmawati (Research in Management of Technology and Business, 2024)
The work productivity of each employee can be seen from the results of the work they have done. This research aims to determine the level of employee work productivity, what factors influence employee work productivity and how to increase employee work productivity. The method used in this research is a quantitative descriptive method. Research location at PT. Indospray Perkasa with a population of 268 people in the company and a sample size of 100 respondents. Data was collected using a questionnaire with a Likert scale. After the data is collected, validity and reliability tests are carried out first. Then the data was analyzed using factor analysis with the SPSS 25 tool. The results showed that the level of employee work productivity at PT Indospray Perkasa was quite high, seen from these 21 indicators, it was formed into 5 groups with an MSA value of more than 5 this factor is believed to influence work productivity PT employees. Indospray Perkasa, namely, education and training, knowledge, number of employees, health, attitudes and behavior. Ways to increase employee work productivity: provide regular training to employees, employees' knowledge of using facilities and their work must be further improved, nutrition and health checks must be further improved, employee attitudes and behavior must also be further improved.